Editorial: Stop Killing Healthcare Workers in South Sudan - Edward Eremugo Kenyi (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2021)
The targeting of healthcare workers in South Sudan must stop. Healthcare and humanitarian workers are there to serve our communities. They do not distinguish patients by their race, ethnicity, culture, language, or geographical location. They are there to save lives, and they should be protected, a responsibility that falls squarely on the Government, be it local or state.